Import substitution processesin Russian industry: theoretical and practical aspects - N. M. Tyukavkin; V. Yu. Anisimova (Модернизация, инновация, развитие, 2023)
Purpose: of the work is to study the main aspects of Russian import substitution in the context of modern political transformations. Methods: the work uses a systematic approach, the induction-deduction method, the method of assessments and scientific abstractions, the method of classification and systematization, the methods of information analysis and synthesis, the statistical method and the method of data visualization.Results: the author's definition of the term "import substitution" is revealed, which differs from the rest by focusing on the production of innovative and high-tech products both in the domestic and foreign markets with the full support of the state. The problematic issues hindering the development of import substitution processes and reducing the effectiveness of this process in the Russian Federation are identified, which can be overcome and solved if we take into account the world experience of successful import substitution and analyze the indicators of the innovation policy of the Russian economy over the past few years. The key features of import substitution as an economic process are highlighted using statistical information on the share of high-tech products of knowledge-intensive industries in the country's GDP under sanctions. The problems hindering the development and reducing the effectiveness of import substitution processes in the Russian Federation are also disclosed, as well as ways to solve them based on world practice are substantiated. Possible trajectories of the state policy for the development of import substitution have been identified.Conclusions and Relevance: the essence of import substitution should take into account both socio-economic and political factors, which will allow the state to develop steadily in the economic and industrial spheres. Measures to increase the competitiveness of products produced on the domestic market can be the modernization of the technological base of an industrial enterprise, an increase in its efficiency indicators and an emphasis on the production of goods that can withstand healthy competition and have increased added value. When implementing the import substitution policy, it is necessary to improve the industrial complex of Russia and transition to an innovative type of economic development model.